Distribution and genetic variability of alfalfa dwarf virus, a cytorhabdovirus associated with alfalfa dwarf disease in Argentina - Samarfard, Samira; Bejerman, Nicolas Esteban; Dietzgen, Ralf Georg (Springer, 2018)
In 2010, a novel cytorhabdovirus named alfalfa dwarf virus (ADV) was detected for the first time in lucerne crops in Argentina showing dwarfism, in mixed infections with several other viruses. ADV appears to be endemic to Argentina and has not been reported elsewhere. In this study, we have investigated the genetic variability of ADV based on the complete nucleoprotein (N) gene of 13 isolates from different lucerne-growing regions in Argentina. Phylogenetic and sequence identity analyses showed that all ADV isolates are closely related and have not diverged more than 1% in the N gene despite geographical separation. These data provide further evidence that ADV is new to science and emerged and spread very recently. A total of 43 single-nucleotide polymorphisms were identified between the ADV isolates studied. Analysis of N gene ORF sequence revealed a mutational bias, with more transitions than transversions. In all cases, the ratio of non-synonymous/synonymous nucleotide changes was < 1, indicating that ADV N gene is under predominantly purifying selection.